Faktor-Faktor yang Mempengaruhi Ibu Hamil dalam Melakukan Perawatan Payudara di UPTD Puskesmas Aramo Tahun 2023 - Endarni Laia; Basaria Manurung; Emma Dosriamaya Noni Br Simanjuntak (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnancy is a special condition for a woman as a prospective mother, because during pregnancy there will be physical changes that affect her life. During pregnancy there will be many changes, both physical, social and mental changes. Pregnant women must have adequate nutrition, because the nutrition obtained will be used for themselves and their fetuses. For pregnant women, basically all nutrients require additional, but what is often lacking is protein energy and some minerals such as iron. This study aims to determine the Factors That Influence Pregnant Women in Carrying Out Breast Care at the Aramo Health Center UPTD in 2023. This type of research is an analytical survey study with a cross-sectional method approach. The population is pregnant women with a total of 52 people in April-May 2023. The number of samples used was 52 people obtained using the Total sampling technique. The data analysis technique uses chi square. the results obtained in this study were from 42 respondents, there was a Relationship between Education and Breast Care at the Aramo Health Center UPTD in 2023 showing that the p value = 0.032 <0.05. there was a Relationship between Age and Breast Care at the Aramo Health Center UPTD in 2023 showing that the p value = 0.024 <0.05. there was a Relationship between Parity and Breast Care at the Aramo Health Center UPTD in 2023 showing that the p value = 0.021 <0.05. there was a Relationship between Knowledge and Breast Care at the Aramo Health Center UPTD in 2023 showing that the p value = 0.021 <0.05. there was a Relationship between Attitudes towards Breast Care at the Aramo Health Center UPTD in 2023 showing that the p value = 0.021 <0.05. It is recommended for Health Workers to increase counseling related to Breast Care.